Internalization of Islamic Education in the Death Gatherings in the Sungai Kapih Community of Samarinda - Mulyani, Mulyani; Hunainah, Hunainah; Syarif, Ahmad (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2025)
This research examines the role of the Rukun Death Association in internalizing Islamic education in the Sungai Kapih community, Samarinda. With a qualitative approach, data was collected through in-depth interviews with association members. The research results show that the Rukun Death tradition functions not only as a social ritual, but also as an effective educational tool in strengthening understanding and appreciation of Islamic teachings. Members who are actively involved in this activity show an increased understanding of Islamic values, such as empathy, solidarity and concern for others. In addition, this tradition helps reduce fear of death, providing a positive perspective on the natural processes of life. This research emphasizes the importance of strengthening similar traditions to support religious education in society, as well as creating communities that are more cohesive and supportive of each other in the face of loss..